Pembangunan Aplikasi Monitoring Jaringan Berbasis Mobile pada Sistem Operasi Android di Dinas Komunikasi dan Informatika Kota Bandung - Rizal Dzulkarnaen; Eka Maryanto (LPPM STMIK AMIK BANDUNG, 2019)
Based on the results of research conducted at the Bandung City Communication and Information Service, data was obtained that the problem with DISKOMINFO is that the network monitoring application that is owned is cacti network, the application only shows on the monitor screen of the DISKOMINFO control room and if there is a problem on the network, for example, if it is not properly connected, the network technician does not immediately know this because there is no notification directly to the network technology. To overcome these problems, as a solution the author recommends to build and implement network monitoring in activities on the use of smartphones, namely Android applications so that the application can be used by network technicians to simplify and speed up the process of monitoring in real time and wherever it is because the system will immediately provide notification according to network problems that occur. The method used in this study is the literature method and interview where data collection problems will be a reference for a solution. In the construction of this application the author uses the JAVA programming language and database storage using MySQL. The author also uses UML (Unified Modeling Language) in helping system design analysis. The Android-based network monitoring application that is built can be used by network technicians of the Bandung City Communication and Information Service Office, as a support for its work, which is monitoring the network according to notifications received from the system in the Bandung city government environment in real time